"Islamic Medicine": A true discipline for the 21st century or quackery?. (March 2022) - Mayberry, John
The purpose of this review is to consider the position of "Islamic Medicine" and whether it is a legitimate form of clinical care or quackery. The analysis is based on published work together with an identification of themes derived from testimonials on practitioners' websites, as well as a consideration of how such therapies are considered in medical search engines. "Islamic Medicine" covers Traditional or Yunani practice, Prophetic Medicine, Hijama and Ruqya. Their origins are discussed and, subsequently, current-day practice and its relationship to allopathic medicine. Reasons for antagonism to modern medicine are considered and the absence of a rational basis for many of the views expressed. In the case of Yunani medicine, its pre-Islamic origins are identified together with the impact of anti-colonialism and the potential role of clerics in wishing to distance medical care from Galenic concepts. In the case of Hijama, the absence of effective training and regulation and its promotion as a "lost sunna" are discussed alongside claims for miraculous cures. The movement of Ruqyah away from Qur'anic recitation in support of the sick towards a popularised approach to dealing with magic and possession is considered, together with consequential adverse publicity in the media. The consequences of a failure to adopt training practices for Yunani medicine, as recommended by the WHO, are identified. Accredited detailed courses monitored by external statutory regulatory agencies, based in institutions committed to providing the best healthcare, and supporting research would allow "Islamic Medicine" to become a significant role player in contemporary clinical practice and stop present-day quackery.